Corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold, preparation method and application

By optimizing the composition and process of magnesium alloy, corrosion-resistant and antibacterial magnesium alloys for bone repair stents were developed, which solved the problem of the rapid degradation rate of magnesium alloy implants and the complex production process, achieved improvement of corrosion resistance and antibacterial properties of magnesium alloys, adapted to different patient needs, and reduced production costs and time.

CN119265465BActive Publication Date: 2025-03-28SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411823373.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Due to the rapid degradation rate of existing magnesium alloy implants, magnesium ions exceeding the normal range of the human body, causing symptoms such as muscle paralysis and hypotension in the biological matrix. At the same time, the production process is complex, the cycle is long and the cost is high, making it difficult to adapt to the needs of different patients.

Method used

By optimizing the alloy composition and process, a corrosion-resistant and antibacterial magnesium alloy for bone repair stent was developed, and elements such as Cu, Zn, Ca, Al were added, and prepared using aerosolized powder making and laser powder bed melting processes.

Benefits of technology

It significantly improves the corrosion resistance and antibacterial properties of magnesium alloys, reduces production costs and time, adapts to the needs of different patients, and improves the biocompatibility and safety of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265465B_ABST
    Figure CN119265465B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of metal medical implant materials, and discloses a corrosion-resistant and antibacterial magnesium alloy for bone repair scaffolds, a preparation method and an application thereof, which is composed of the following components in mass percentage: Zn: 3.5-7.0%, Ca: 0.1-0.5%, Al: 0.1-0.3%, Cu: 0.05-0.1%, and the balance is Mg; and also discloses an application and a preparation method thereof. The present invention can significantly improve the corrosion resistance of magnesium alloy implants, and can also effectively exert an antibacterial effect; it is more convenient to carry out personalized modeling and forming processing of implants according to the differentiated requirements of different patients for the shape and size of implants, and can also greatly shorten the treatment time and reduce the treatment cost, and accelerate the recovery process of patients, and has a very broad application prospect; the present invention adopts a laser powder bed melting process to prepare magnesium alloys, which has the advantages of short process, high forming accuracy and good mechanical properties, and is very suitable for the manufacture of small batches of high value-added products with complex structures, and significantly shortens the production cost and time of medical implants with complex structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal medical implant materials, and in particular to a corrosion-resistant and antibacterial magnesium alloy for a bone repair stent, a preparation method and an application thereof. Background Art

[0002] Magnesium is an essential non-trace element that participates in the synthesis and metabolism of human substances. Its extremely low standard electrode potential makes it easily absorbed by human body fluids and excreted from the body, so it has good biocompatibility with the human body. Difficult-to-degrade biomedical alloys, represented by titanium alloys, will bring a series of complications after being implanted in the human body. In addition to long-term medication, patients also need to undergo a second surgery to remove orthopedic implants, which greatly increases the economic and physical burden on patients. Magnesium alloys have good biodegradability and will be completely degraded within a certain period of time after entering the human body, which can effectively reduce the burden on patients.

[0003] At present, the clinical application fields of magnesium alloys include cardiovascular, orthopedic, general surgery and dentistry, and the applied products include cardiovascular stents, bone repair stents, human duct stents, etc. The difficulty of the current biomedical use of magnesium alloys lies in the fact that the magnesium alloy itself has an excessively high degradation rate. When it degrades too quickly, the magnesium ions that are not released in time will exceed the normal range of the human body, causing symptoms such as muscle paralysis and hypotension in the biological matrix. In addition, the current magnesium alloy implants are mostly produced using the process of casting + thermal deformation + machining, which has a long production cycle, low efficiency and high cost, and it is difficult to effectively adapt to the application characteristics of different individual patients with different needs.

[0004] In order to avoid the disadvantages of low corrosion resistance of existing magnesium alloys and the susceptibility to inflammation caused by long-term existence of implants, the present invention has developed a new type of Cu-containing corrosion-resistant and antibacterial magnesium alloy. Summary of the invention

[0005] Based on the above problems, the present invention provides a corrosion-resistant and antibacterial magnesium alloy for bone repair scaffolds, a preparation method and an application thereof. The present invention significantly improves the corrosion resistance and antibacterial properties of the corrosion-resistant and antibacterial magnesium alloy by optimizing the alloy composition and process, while significantly shortening the production cost and time of medical implants with complex structures, greatly expanding the application prospects of biomedical magnesium alloys in this field.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The corrosion-resistant and antibacterial magnesium alloy used for bone repair scaffolds is composed of the following components in mass percentage: Zn: 3.5-7.0%, Ca: 0.1-0.5%, Al: 0.1-0.3%, Cu: 0.05-0.1%, and the balance is Mg.

[0008] Furthermore, the mass percentage of Zn is 4.5%-7.0%.

[0009] Furthermore, the grain size of the corrosion-resistant and antibacterial magnesium alloy is between 0.5 and 2 μm.

[0010] Furthermore, the corrosion-resistant and antibacterial magnesium alloy contains nanocrystals.

[0011] Furthermore, the corrosion-resistant and antibacterial magnesium alloy contains a dispersed small-sized second phase, and the components of the small-sized second phase include Mg 2 Ca, Ca 2 Mg 6 Zn 3 and Mg 17 Al 12 .

[0012] In order to solve the above technical problems, the present invention also provides the use of the corrosion-resistant and antibacterial magnesium alloy for bone repair scaffolds in the preparation of bone repair scaffold products.

[0013] In order to solve the above technical problems, the present invention also provides a method for preparing a corrosion-resistant and antibacterial magnesium alloy for a bone repair scaffold, comprising the following steps:

[0014] S1: Smelting

[0015] Add high-purity raw materials into the induction melting furnace according to the set ratio for melting. The melting temperature is controlled at 700-750℃, and a protective atmosphere is used to prevent magnesium oxidation.

[0016] S2: Refining

[0017] Refining agents are added during the smelting process to remove impurities and ensure the purity of the alloy. After refining, slag and impurities are removed;

[0018] S3: Aerosol powder making

[0019] The molten alloy after the treatment in step S2 is subjected to gas atomization powdering in a protective atmosphere, the melt temperature is controlled at 680-720° C., and the atomizer nozzle pressure is controlled at 5-8 MPa;

[0020] S4: Powder Screening

[0021] The aerosolized powder is vacuum dried and sieved under a protective atmosphere to obtain a particle size of 38 μm. After sieving, the powder is vacuum sealed.

[0022] S5: LPBF forming

[0023] The LPBF forming process is carried out in an EOS M290 device. First, 5 kg of alloy powder treated in step S4 is loaded into the powder chamber. The protective atmosphere during the forming process is argon gas, and the oxygen content in the protective atmosphere is less than 500 ppm. The laser power of LPBF forming is 100-200 W, the powder bed thickness is 30 μm, the scanning speed is 300-800 mm / s, and the scanning interval is 30-50 μm.

[0024] S6: Stress relief annealing

[0025] The material after the step S5 is subjected to stress relief annealing treatment at 225° C. for 2 hours to eliminate the thermal stress generated during the printing process, thereby avoiding stress corrosion.

[0026] S7: Aging treatment

[0027] The annealed alloy material is subjected to aging treatment to improve strength, the aging temperature is 175°C, and the holding time is 24-48h;

[0028] S8: Surface finishing

[0029] The key matching surfaces of the heat-treated alloy material are subjected to surface finishing to obtain the final product.

[0030] Furthermore, the protective atmosphere in step S1 is argon, and the refining agent in step S2 is RJ-2.

[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: the magnesium alloy obtained by optimizing the alloy composition of the present invention can significantly improve the corrosion resistance of the magnesium alloy implant, and can also effectively exert an antibacterial effect through the continuous release of Cu ions during service, so that the magnesium alloy of the present invention has good corrosion resistance and antibacterial properties in the human body fluid environment;

[0032] The magnesium alloy obtained by the present invention has good atomization powder making and laser melting forming properties, and is more convenient for personalized modeling and forming of implants according to the differentiated needs of different patients for the shape and size of implants. At the same time, it can greatly shorten the treatment time and reduce the treatment cost, and accelerate the recovery process of patients, and has a very broad application prospect.

[0033] The present invention adopts the laser powder bed melting process to prepare magnesium alloy, which has the advantages of short process, high forming accuracy and good mechanical properties. It is very suitable for the manufacture of small batches of high value-added products with complex structures, and significantly shortens the production cost and time of medical implants with complex structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic diagram of the LPBF forming path and a real picture of the forming process in an embodiment of the present invention;

[0035] Figure 2 It is a three-dimensional surface profile diagram of the LPBF formed sample in Example 1 of the present invention and the comparative example;

[0036] Figure 3 It is the corrosion morphology diagram in the embodiment of the present invention and the comparative example;

[0037] Figure 4 It is a mechanical property (tensile) curve diagram in the embodiment of the present invention. DETAILED DESCRIPTION

[0038] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0039] Embodiment 1:

[0040] In this embodiment, the corrosion-resistant and antibacterial magnesium alloy is prepared by the following ratio: 6.5% zinc, 0.45% calcium, 0.2% aluminum, 0.05% copper, and the balance is magnesium.

[0041] Then, the preparation method of the corrosion-resistant and antibacterial magnesium alloy described above (the invention content part of the specification) is followed to carry out smelting, refining, gas atomization powder making, powder screening, LPBF forming, stress relief annealing, aging treatment and surface finishing. The LPBF forming parameters are: powder bed thickness of 30 μm, scanning spacing of 30 μm, laser power of 120 W, and scanning speed of 450 mm / s.

[0042] The resulting print is 100×10×10mm 3 Through experimental tests, the magnesium alloy block obtained in this embodiment has a density of 89.8%, a surface roughness of 17±0.4μm, a yield strength of 198MPa, a tensile strength of 285MPa, an elongation of 9.8%, and a corrosion rate of 0.82mg / cm2 after immersion in Hank's solution. 2 / day, the E. coli colony test showed that the 108-hour inhibition rate was 75%.

[0043] Embodiment 2:

[0044] In this embodiment, the corrosion-resistant and antibacterial magnesium alloy is prepared by the following ratio: 4.5% zinc, 0.25% calcium, 0.25% aluminum, 0.1% copper, and the balance is magnesium.

[0045] Then, according to the preparation method of the corrosion-resistant and antibacterial magnesium alloy mentioned above (the invention content part of the specification), smelting, refining, gas atomization powder making, powder screening, LPBF forming, stress relief annealing treatment, aging treatment and surface finishing processing are carried out. Among them, the LPBF forming parameters are: powder bed thickness is 30μm, scanning spacing is 40μm, laser power is 150W, and scanning speed is 500mm / s.

[0046] The resulting print is 100×10×10mm 3 The experimental test shows that the magnesium alloy block has a density of 99.0%, a surface roughness of 15±0.3μm, a yield strength of 224MPa, a tensile strength of 302MPa, an elongation of 10.5%, and a corrosion rate of 0.8mg / cm2 after immersion in Hank's solution. 2 / day, the E. coli colony test showed that the 108-hour inhibition rate was 85%.

[0047] Embodiment 3:

[0048] In this embodiment, the corrosion-resistant and antibacterial magnesium alloy is prepared by the following ratio: 6.0% zinc, 0.36% calcium, 0.25% aluminum, 0.05% copper, and the balance is magnesium.

[0049] Then, the preparation method of the corrosion-resistant and antibacterial magnesium alloy described above (the invention content part of the specification) is followed to carry out smelting, refining, gas atomization powder making, powder screening, LPBF forming, stress relief annealing, aging treatment and surface finishing. Among them, the LPBF forming parameters are: powder bed thickness of 30μm, scanning spacing of 40μm, laser power of 200W, and scanning speed of 800mm / s.

[0050] The resulting print is 100×10×10mm 3 The experimental test shows that the magnesium alloy block has a density of 99.1%, a surface roughness of 14±0.2μm, a yield strength of 245MPa, a tensile strength of 334MPa, an elongation of 12%, and a corrosion rate of 0.75mg / cm2 after immersion in Hank's solution. 2 / day, the E. coli colony test showed that the 108-hour inhibition rate was 78%.

[0051] Comparison example:

[0052] In this embodiment, the corrosion-resistant and antibacterial magnesium alloy is prepared by the following ratio: 3.2% zinc, 0.9% calcium, 0.4% aluminum, 0.16% copper, and the balance is magnesium.

[0053] Then, the preparation method of the corrosion-resistant and antibacterial magnesium alloy described above (the invention content part of the specification) is followed to carry out smelting, refining, gas atomization powder making, powder screening, LPBF forming, stress relief annealing, aging treatment and surface finishing. Among them, the LPBF forming parameters are: powder bed thickness of 30μm, scanning spacing of 40μm, laser power of 100W, and scanning speed of 800mm / s.

[0054] The resulting print is 100×10×10mm 3 The experimental test shows that the magnesium alloy block has a density of 85%, a surface roughness of 28±0.4μm, a yield strength of 145MPa, a tensile strength of 226MPa, an elongation of 5.5%, and a corrosion rate of 1.8mg / cm2 after immersion in Hank's solution. 2 / day, the E. coli colony test showed that the 108-hour inhibition rate was 60%.

[0055] See attached Figure 1 , which is a schematic diagram of the LPBF forming path used in the above-mentioned embodiment and the comparative example ((a) in FIG1 ) and a real picture of the forming process ((b) in FIG1 ). The surface profile of the LPBF formed sample reflects the surface roughness of the sample, see FIG1 Figure 2 . See attached Figure 3 , is the corrosion morphology diagram. See attached Figure 4 , which is a mechanical property (tensile) curve diagram of Examples 1 to 3.

[0056] The measurement data of Examples 1 to 3 and the comparative example are organized in the following table.

[0057]

[0058] It can be seen more clearly from the table that Examples 1 to 3 all have good forming properties (density close to or exceeding 99%), the formed parts have low surface roughness, and only a small amount of processing is required to obtain a final product with good precision. However, due to composition and process deviations, the density of the control example is only 85%, there are many holes inside, and the surface layer also shows poor surface roughness due to severe splashing during the forming process. Due to the difference in density, the mechanical properties of Examples 1 to 3 are better than those of the control example in all aspects. In addition, the density of the formed part has a great influence on its corrosion resistance: the product film formed in Examples 1 to 3 during the corrosion process can form a good coverage of the remaining matrix alloy, thereby showing relatively good corrosion resistance (see Appendix). Figure 3 ); However, due to the presence of many holes inside the control example, the corrosion product film cannot form a dense coverage on the internal alloy matrix and thus exhibits poor corrosion resistance (see Appendix Figure 3 ).

[0059] Since Examples 1 to 3 have good corrosion resistance, they can inhibit the growth of bacteria by continuously and slowly releasing copper ions, thus showing a good 108-hour antibacterial rate. The control example has good antibacterial properties in the early stage due to the rapid escape of copper ions, but as the test time is extended, its antibacterial properties significantly decrease due to the rapid decrease in copper ion concentration.

[0060] In summary, compared with the control example, Examples 1 to 3 have significant advantages.

[0061] The above is an embodiment of the present invention. The above embodiments and the specific parameters in the embodiments are only for the purpose of clearly describing the invention verification process, and are not intended to limit the patent protection scope of the present invention. The patent protection scope of the present invention is still subject to its claims. Any equivalent structural changes made by using the contents of the description and drawings of the present invention should be included in the protection scope of the present invention.

Claims

1. A corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold, characterized in that: It is composed of the following components in percentage by mass: Zn: 3.5-7.0%, Ca: 0.1-0.5%, Al: 0.1-0.3%, Cu: 0.05-0.1%, the balance is Mg; The method for preparing the corrosion-resistant and antibacterial magnesium alloy of the bone repair scaffold comprises the following steps: S1: Smelting Add high-purity raw materials into the induction melting furnace according to the set ratio for melting. The melting temperature is controlled at 700-750℃, and a protective atmosphere is used to prevent magnesium oxidation. S2: Refining Refining agents are added during the smelting process to remove impurities, and slag and impurities are removed after refining is completed; S3: Aerosol powder making The molten alloy after the treatment in step S2 is subjected to gas atomization powdering in a protective atmosphere, the melt temperature is controlled at 680-720° C., and the atomizer nozzle pressure is controlled at 5-8 MPa; S4: Powder Screening The aerosolized powder is vacuum dried and sieved under a protective atmosphere to obtain a particle size of 38 μm. After sieving, the powder is vacuum sealed. S5: LPBF forming The LPBF forming process is carried out in an EOS M290 device. First, 5 kg of alloy powder treated in step S4 is loaded into the powder chamber. The protective atmosphere during the forming process is argon gas, and the oxygen content in the protective atmosphere is less than 500 ppm. The laser power of LPBF forming is 100-200 W, the powder bed thickness is 30 μm, the scanning speed is 300-800 mm / s, and the scanning interval is 30-50 μm. S6: Stress relief annealing The material after the step S5 is subjected to stress relief annealing treatment, and the stress relief annealing treatment conditions are 225° C. and 2 h; S7: Aging treatment The annealed alloy material is subjected to aging treatment to improve strength, the aging temperature is 175°C, and the holding time is 24-48h; S8: Surface finishing The key matching surfaces of the heat-treated alloy material are subjected to surface finishing to obtain the final product.

2. The corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold according to claim 1, characterized in that: The mass percentage of Zn is 4.5%-7.0%.

3. The corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold according to claim 1 or 2, characterized in that: The grain size of the corrosion-resistant and antibacterial magnesium alloy is between 0.5 and 2 μm.

4. The corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold according to claim 1 or 2, characterized in that: The corrosion-resistant and antibacterial magnesium alloy contains nanocrystals.

5. The corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold according to claim 1 or 2, characterized in that: The corrosion-resistant and antibacterial magnesium alloy contains a dispersed small-sized second phase, and the components of the small-sized second phase include Mg2 Ca, Ca2 Mg6Zn3 and Mg 17 Al 12 .

6. The corrosion-resistant and antibacterial magnesium alloy for bone repair scaffold according to claim 1, characterized in that: The protective atmosphere in step S1 is argon, and the refining agent in step S2 is RJ-2.

7. Use of the corrosion-resistant and antibacterial magnesium alloy for bone repair scaffolds according to claim 1 or 2 in the preparation of bone repair scaffold products.

Citation Information

Patent Citations

  • High-performance degradable biological magnesium alloy material and preparation method thereof

    CN115198155A